Assessing Colorectal Cancer Awareness and Preventive Lifestyle Practices in the United Arab Emirates: A Comparative Study of Risk Groups. - Mohamedali, Lamees; Al-Kubaisi, Mohammed; Alhaj Ahmad, Shahem; Haroon, Samiullah; Alshalkhaty, Albara; Mohammed Hussein, Daniah; Alhaj Ahmad, Karam; Abueida, Mohammed; Talaat, Iman (Journal of Community Health, 2025)
Colorectal cancer (CRC) is the third most prevalent cancer worldwide, with its incidence rising in the Middle East. In the United Arab Emirates (UAE), higher numbers of younger individuals are being diagnosed, likely due to unhealthy lifestyle habits. This study aims to investigate the relationship between CRC awareness and preventive lifestyle practices among varying risk groups. A cross-sectional study was conducted among the adult UAE population between October and December 2024. Data was collected using a self-administered questionnaire consisting of sociodemographics, CRC risk assessment, screening eligibility, and the Bowel Cancer Awareness Measure (BoCAM). Adherence to cancer-preventive lifestyle behaviors was assessed using the WCRF/AICR Score. 910 participants were surveyed. The median CRC knowledge score was 10 out of 22 (IQR = 6, 13). 57.4% lacked confidence in recognizing CRC symptoms. Higher knowledge scores were significantly associated with female sex, non-Emirati nationality, higher education, employment or studies in healthcare, and a first-degree family history of CRC. Despite having the highest knowledge levels, the higher CRC-risk group exhibited cancer-preventive behaviors comparable to the average and no-risk groups. Risk factor knowledge did not influence adherence to healthy dietary habits but was positively associated with increased physical activity. Few were aware of a CRC screening program (29%) and the recommended screening age (7%). Only 10.1% of screening-eligible participants had undergone CRC screening. Knowledge on CRC in the UAE is relatively low, with a gap between the public's awareness and their lifestyle practices. This calls for targeted educational campaigns and early detection strategies, particularly among higher-risk groups.